2019
DOI: 10.1101/747709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstruction of nine thousand years of agriculture-based diet and impact on human genetic diversity in Asia

Abstract: Domestication of crops and animals during the Holocene epoch played a critical role in shaping human culture, diet and genetic variation. This domestication process took place across a span of time and space, especially in Asia. We hypothesize that domestication of plants and animals around the world must have influenced the human genome differentially among human populations to a far greater degree than has been appreciated previously. The range of domesticated foods that were available in different regions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This relationship has resulted in genetic alterations in both human and domesticated crop genomes. The human genome shows genetic footprints in genes related to specific diets (Raj et al 2019), and the domestication of crop plants and their continuous adaptation to our needs resulted in the loss of genetic diversity. Modern elite varieties, which are the result of cross-breeding, show yet lower genetic diversity when compared to their landrace progenitors (Raj et al 2019).…”
Section: Global Seedbanks: An Untapped Resource For Nutritionally Ben...mentioning
confidence: 99%
“…This relationship has resulted in genetic alterations in both human and domesticated crop genomes. The human genome shows genetic footprints in genes related to specific diets (Raj et al 2019), and the domestication of crop plants and their continuous adaptation to our needs resulted in the loss of genetic diversity. Modern elite varieties, which are the result of cross-breeding, show yet lower genetic diversity when compared to their landrace progenitors (Raj et al 2019).…”
Section: Global Seedbanks: An Untapped Resource For Nutritionally Ben...mentioning
confidence: 99%
“…Several large longitudinal studies showed that the intake of animal protein was significantly associated with the risk of T2D [ 13 , 14 , 15 , 16 , 17 ]. In the context of rapid urbanisation and nutrition transition, interactions between Westernised diet, lifestyle and genetic factors have further escalated T2D prevalence in Asia [ 18 , 19 ]. In South Asians, several single nucleotide polymorphisms (SNPs) have been associated with adiposity [ 20 , 21 , 22 , 23 ], insulin resistance [ 24 ], pancreatic β-cell function [ 20 , 25 , 26 ] and T2D [ 20 , 22 , 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%